Some Results on Strict Graded Categorical Groups. (26th August 2013) - Tien Quang, Nguyen; Thi Kim Phung, Che
Abstract : We present some applications of strict graded categorical groups to the construction of the obstruction of an equivariant kernel and to the classification of equivariant group extensions which are central ones. The composition of a graded categorical group and an equivariant group homomorphism is also determined.